2019
DOI: 10.1051/0004-6361/201935056
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved GRB polarization with POLAR and GBM

Abstract: Context. Simultaneous γ-ray measurements of γ-ray burst spectra and polarization offer a unique way to determine the underlying emission mechanism(s) in these objects, as well as probing the particle acceleration mechanism(s) that lead to the observed γ-ray emission. Aims. We examine the jointly observed data from POLAR and Fermi-GBM of GRB 170114A to determine its spectral and polarization properties, and seek to understand the emission processes that generate these observations. We aim to develop an extensib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 46 publications
2
58
1
Order By: Relevance
“…Then, the on-set of afterglow emission occurs when the external shock develops as the jet interacts with the surrounding media. This figure is courtesy of Dan Kocevski (private communication) et al 2019; Burgess et al 2019). Continued advancement in these studies is a promising method to understand the prompt emission mechanism of GRBs.…”
Section: 6mentioning
confidence: 91%
“…Then, the on-set of afterglow emission occurs when the external shock develops as the jet interacts with the surrounding media. This figure is courtesy of Dan Kocevski (private communication) et al 2019; Burgess et al 2019). Continued advancement in these studies is a promising method to understand the prompt emission mechanism of GRBs.…”
Section: 6mentioning
confidence: 91%
“…Therefore, here we report an upper limit on polarisation fraction as 37% and 50% at 1.5σ (86%) and 2σ (90%) confidence level respectively, for one parameter of interest. The low polarisation fraction across the emission episode can be due to (i) varying polarisation angle as a function of time within the episode, despite high polarisation being high (Götz et al 2009;Zhang et al 2019;Burgess et al 2019b;Sharma et al 2019) or (ii) the observed emission within 1/Γ is inherently weakly polarised (Toma et al 2009, also see section 6.4).…”
Section: Polarisation Measurementsmentioning
confidence: 99%
“…Linear polarisation measurement of the prompt emission of GRBs is a powerful tool, in addition to spectral analysis, to strongly constrain the radiation process, geometry of the emitting region and the composition of the GRB outflow (Covino & Gotz 2016). Currently, polarisation measurement of prompt emission has been reported for only a handful of cases (Wigger et al 2004;Willis et al 2005;McGlynn et al 2007;Götz et al 2009;McGlynn et al 2009;Yonetoku et al 2011Yonetoku et al , 2012Götz et al 2013Götz et al , 2014Zhang et al 2019;Burgess et al 2019b;Chand et al 2018Chand et al , 2019Sharma et al 2019;Chattopadhyay et al 2019; for a recent review see McConnell 2017). Linear polarisation has also been measured in early optical afterglows of a few GRBs (Wijers et al 1999;Covino et al 2002;Greiner et al 2003;King et al 2014;Gorbovskoy et al 2016;Troja et al 2017;Laskar et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…After the launch of Fermi in 2008, with the spectral data of higher quality, the former two patterns are confirmed to be dominated: "hard-to-soft" for about two-thirds and "flux-tracking" for about one-third (e.g., Lu et al 2012;Yu et al 2018). The physical origin of these E p evolution patterns still remain unsolved, though some scenarios have been proposed in the literature (e.g., Liang et al 1997;Ryde & Svensson 1999;Medvedev 2006;Zhang 2011;Zhang & Yan 2011;Deng & Zhang 2014;Uhm & Zhang 2014Oganesyan et al 2018Oganesyan et al , 2019Uhm et al 2018;Burgess et al 2019).…”
Section: Introductionmentioning
confidence: 99%